A Phase 2a Randomized Study to Evaluate the Safety and Immunogenicity of the 1790GAHB Generalized Modules for Membrane Antigen Vaccine against Shigella sonnei Administered Intramuscularly to Adults from a Shigellosis-Endemic Country - Obiero, Christina W.; Ndiaye, Augustin G. W.; Sciré, Antonella Silvia; Kaunyangi, Bonface M.; Marchetti, Elisa; Gone, Ann M.; Schütte, Lena Dorothee; Riccucci, Daniele; Auerbach, Joachim; Saul, Allan; Martin, Laura B.; Bejon, Philip; et al. (Frontiers in Immunology, 2017)
Shigellosis is a mild-to-severe diarrheal infection caused by the genus Shigella and responsible for significant morbidity and mortality worldwide. We evaluated the safety and immunogenicity of an investigational Shigella sonnei vaccine (1790GAHB) based on Generalized Modules for Membrane Antigens (GMMA) in Kenya, a Shigella-endemic country. This phase 2a, observer-blind, controlled study (NCT02676895) enrolled and randomized 74 healthy adults aged 18–45 years, of whom 72 were vaccinated. Participants, randomized with a 1:1:1 ratio, received 2 vaccinations with the 1790GAHB vaccine at doses of either 1.5/25 μg of O antigen/protein (group 1.5/25 μg) or 5.9/100 μg (group 5.9/100 μg) at day [D] 1 and D29, or vaccination with a quadrivalent meningococcal vaccine at D1 and diphtheria, tetanus and acellular pertussis vaccine at D29 (control group). Solicited and unsolicited adverse events (AEs), serious AEs and AEs of special interest (neutropenia and reactive arthritis) were collected. Anti-S. sonnei LPS serum IgG geometric mean concentrations (GMC) were evaluated at D1, D29 and D57 and compared to anti-S. sonnei LPS antibody levels in convalescent patients naturally-exposed to S. sonnei. The percentages of participants with seroresponse were calculated. The most frequently reported solicited local and systemic AEs across all groups were pain and headache, respectively. Only 1 case of severe systemic reaction was reported (severe headache after first vaccination in group 5.9/100 µg). Ten cases of transient and asymptomatic neutropenia, assessed as probably or possibly related to vaccination, were recorded in 6 participants from all 3 groups. No other serious AEs were reported. Despite very high baseline anti-S. sonnei LPS serum IgG levels, the 1790GAHB vaccine induced robust antibody responses. At D29, GMC increased 2.10- and 4.43-fold from baseline in groups 1.5/25 µg and 5.9/100 µg, respectively, whereas no increase was observed in the control group. Antibody titers at D57 were not statistically different from those at D29. Seroresponse was 68% at D29 and 90% at D57 in group 1.5/25 μg, and 96% after each vaccination in group 5.9/100 μg. The 1790GAHB vaccine was well tolerated and, despite very high baseline antibody titers, elicited robust antibody response in a population of African adults, regardless of GMMA content